Micro-channels array device fabricated via two photon lithography for cell migration studies in Neuroblastoma metastatic disseminationAll original data are available at: . - Sara Micheli; Caterina Piunti; Elisa Varaschin; Marianna Peditto; Maria Luz Suarez; Marco Sorgato; Elisa Cimetta (OpenNano)
Detailed studies of cells migration are key in understanding tumors metastatic spread. We used two-photon polymerization (2PP) to create precise microdevices for studying cell migration through micro-channels at a single cell resolution. Micro-channels are designed to mimic the structure of lymphatic vessels, conduits for cell movement in vivo. Neuroblastoma (NB) and human Mesenchymal Stem Cells (MSCs) represent the main tumor and its primary metastatic site. Our results revealed distinctive behaviors of NB and MSCs, both individually and in co-culture, hinting at a tumor-suppressive role of MSCs inhibiting NB migration. Pre-exposure of MSCs to NB-derived extracellular vesicles (EVs) significantly increased their motility towards tumor cells. Our platform more effectively replicates the in vivo environment of metastatic migration, with results providing new insights into the early dissemination of NB. Such microdevices hold great promise for advancing our understanding of metastasis and aiding the development of targeted anti-cancer therapies.